Diversity and Transmission of Gut Bacteria in Atta and Acromyrmex Leaf-Cutting Ants during Development - Zhukova, Mariya; Sapountzis, Panagiotis; Schiøtt, Morten; Boomsma, Jacobus J. (Frontiers in Microbiology, 2017)
The social Hymenoptera have distinct larval and adult stages separated by metamorphosis, which implies striking remodeling of external and internal body structures during the pupal stage. This imposes challenges to gut symbionts as existing cultures are lost and may or may not need to be replaced. To elucidate the extent to which metamorphosis interrupts associations between bacteria and hosts, we analysed changes in gut microbiota during development and traced the transmission routes of dominant symbionts from the egg to adult stage in the leaf-cutting ants Acromyrmex echinatior and Atta cephalotes, which are both important functional herbivores in the New World tropics. Bacterial density remained similar across the developmental stages of Acromyrmex, but Atta brood had very low bacterial prevalences suggesting that bacterial gut symbionts are not actively maintained. We found that Wolbachia was the absolute dominant bacterial species across developmental stages in Acromyrmex and we confirmed that Atta lacks Wolbachia also in the immature stages, and had mostly Mollicutes bacteria in the adult worker guts. Wolbachia in Acromyrmex appeared to be transovarially transmitted similar to transmission in solitary insects. In contrast, Mollicutes were socially transmitted from old workers to newly emerged callows. We found that larval and pupal guts of both ant species contained Pseudomonas and Enterobacter bacteria that are also found in fungus gardens, but hardly or not in adult workers, suggesting they are beneficial only for larval growth and development. Our results reveal that transmission pathways for bacterial symbionts may be very different both between developmental stages and between sister genera and that identifying the mechanisms of bacterial acquisition and loss will be important to clarify their putative mutualistic functions.